Tinjauan Yuridis Terhadap Perjanjian Jual-Beli Dalam Transaksi Elektronik Menurut Pasal 1320 Kitab Undang-Undang Hukum Perdata - Simanungkalit, Jo Brinson; Prastyanti, Rina Arum; Hastuti, Indra (Universitas Muara Bungo, 2025)
The existence of the digital world today is marked by the rapid development of data transmission through information technology called the internet. The development of information technology, especially the internet, has made very gradual changes in the aspects of life in modern society today. Currently, there are many platforms providing modern electronic commerce transactions that utilize technological advances as a medium for implementation or what is commonly called e-commerce. Several problems that often arise in buying and selling transactions via e-commerce include issues regarding agreements, electronic signatures, payment procedures, taxation, legal protection, justice, and methods of resolving disputes that arise. The Government of the Republic of Indonesia has issued Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (UUITE). In Law Number 19 of 2016, the meaning of electronic agreements/contracts is not clearly and firmly explained but only provides general limitations. So the author identifies the problem of regulation and treatment of internet-based sales and purchase agreements and the validity of internet-based sales and purchase agreements according to Article 1320 of the Civil Law..